Explicit Information Reduces Discounting Behavior in Monkeys - Pearson, John; Hayden, Benjamin; Platt, Michael (Frontiers in Psychology, 2010)
Animals are notoriously impulsive in common laboratory experiments, preferring smaller, sooner rewards to larger, delayed rewards even when this reduces average reward rates. By contrast, the same animals often engage in natural behaviors that require extreme patience, such as food caching, stalking prey, and traveling long distances to high quality food sites. One possible explanation for this discrepancy is that standard laboratory delay discounting tasks artificially inflate impulsivity by subverting animals’ common learning strategies. To test this idea, we examined choices made by rhesus macaques in two variants of a standard delay discounting task. In the conventional variant, post-reward delays were uncued and adjusted to render total trial length constant; in the second, all delays were cued explicitly. We found that measured discounting was significantly reduced in the cued task, with discount rates well below those reported in studies using the standard uncued design. When monkeys had complete information, their decisions were more consistent with a strategy of reward rate maximization. These results indicate that monkeys, and perhaps other animals, are more patient than is normally assumed, and that laboratory measures of delay discounting may overstate impulsivity.